Combined effects of entomopathogenic fungi, plant extracts, and biorational insecticides on Morocain endemic bush cricket Eugaster spinulosa Johansson (Orthoptera: Tettigoniidae) infesting Opuntia spp. - El Aalaoui, Mohamed; Rammali, Said; Kamal, Fatima Zahra; Ciobica, Alin; Albert, Cristina; Burlui, Vasile; Novac, Bogdan; Bencharki, Bouchaib; Sbaghi, Mohamed (Frontiers in Microbiology, 2025)
IntroductionEugaster spinulosa Johansson (Orthoptera: Tettigoniidae) poses a serious threat to Opuntia spp. cultivation in Morocco, requiring effective control strategies.MethodsThis study evaluated the individual and combined effects of two entomopathogenic fungi (Alternaria destruens (AD) and A. murispora (AM) at 1010 conidia/mL), three plant extracts (Nicotiana glauca (NG), Capsicum annuum (CA) (Solanaceae), and Ricinus communis (RC) (Euphorbiaceae) at 10% (w/v)), and two biorational insecticides mineral oil at 1000 cc/hl (MO) and potassium salts of fatty acids at 300 cc/hl (PFA)) on E. spinulosa under laboratory (26±2°C, 16:8 L:D photoperiod) and screenhouse conditions (26±2°C, natural light).Results and discussionThe most effective combinations (AM+CA+MO+PFA, AM+RC+MO+PFA, and AM+NG+MO+PFA) significantly reduced egg densities by week 5 to 4.85.1 eggs in the laboratory, and 8.58.9 eggs in the screenhouse, respectively, compared to 26.3 and 44.6 eggs in the untreated controls. Motile stages (nymphs and adults) were also reduced to 2.83.2 individuals in the laboratory and 4.34.6 individuals in the screenhouse, compared to 18.7 and 29.5 individuals in controls. Moderate reductions were observed with single applications of A. murispora (11.5 motile stages, 14.3 eggs) and mineral oil (13.6 motile stages, 16.7 eggs) under screenhouse conditions. Tween 80 showed negligible effects. All effective treatments significantly enhanced plant visual quality, with scores reaching 9.9.3 by week 5, compared to 4.1 in the control group. These findings show that combining A. murispora, C. annuum, R. communis, N. glauca, and biorational insecticides effectively controls E. spinulosa on cactus.